Measuring the Direct and Spillover Effects of Body Worn Cameras on the Civility of Police–Citizen Encounters and Police Work Activities - Braga, Anthony Allan (Journal of quantitative criminology, 2020)
Existing research on the effects of body-worn cameras (BWCs) have found largely consistent results regarding direct significant reductions in citizen complaints and often also report reductions in use of force reports. However, few studies have examined possible spillover effects onto untreated officers. This study explicitly tests for direct and spillover effects of BWCs on the civility of police-citizen encounters and police work activities.